Peningkatan keterampilan masyarakat Desa Rumbio Kabupaten Kampar melalui pengolahan Jahe Merah - Evi Sribudiani; Sonia Somadona; Pebriandi Pebriandi; Defri Yoza; Viny Volcherina Darlis (Unri Conference Series: Community Engagement, 2020)
The people of Rumbio Village are people with an average profession as farmers. The people of Rumbio Village have an economic level at the middle to lower level and need special attention from the government. One way to improve the economic level of the Rumbio village community is by forming their skills in post-harvest processing of agricultural products. This skill is needed for processing agricultural products in this case red ginger. based on this, a community service activity entitled "Improving Community Skills in Rumbio Village, Kampar Regency through Red Ginger Processing" was carried out. The method of application is carried out in the form of socialization and direct practice, namely processing red ginger into instant ginger, this activity is carried out in the meeting hall of the Rumbio Village office with the target community, namely the PKK women of Rumbio village. activity, where the participants were very enthusiastic and contributed to the processing of instant ginger, then the results were also obtained that this instant red ginger can generate profits twice as much as the initial capital spent. Processing of instant ginger is a very promising business opportunity, so it is important to improve the skills of the target community in processing red ginger into instant ginger, the increase is seen from the achievement of the activity indicators, namely technical and non-technical knowledge of making instant red ginger.